Population dynamics of two sympatric intertidal fish species (the shanny, Lipophrys pholis, and long-spined scorpion fish,Taurulus bubalis) of Great Britain - Barrett, C.J.; Johnson, M.L.; Hull, S.L. (Journal of the Marine Biological Association of the United Kingdom, 2016)
The shanny/common blenny (Lipophrys pholis) and long-spined scorpionfish/bullhead (Taurulus bubalis) are commonly encountered, sympatric species within much of Great Britain’s rocky intertidal zones. Despite being prey items of the cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) respectively, and both contributors to the diet of the near-threatened European otter (Lutra lutra), little is known on the population dynamics of the temperate specimens of Great Britain. It is further less known of the degrees of sympatricy between the two fish species and to what extent they are able to coexist. The current study examines spatio-temporal distributions and abundances at various resolutions: monthly population dynamics of both species along England’s Yorkshire coast and seasonal population dynamics along the Yorkshire coast and around the Isle of Anglesey, Wales. Studies of their abundances, sizes, degrees of rock pool co-occurrence and diel activities are further examined, which indicate coexistence is maintained when interspecific co-occurrence takes place only between specimens of similar sizes, thus demoting size-related dominance hierarchies.